HOT WEATHER IN THE DEVELOPMENT OF POULTRY (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
this article covers the importance of poultry farming in agriculture, its role in ensuring food safety and the development characteristics of modern poultry industries.